Upaya Meningkatkan Bicara Anak Autis Melalui Pendekatan Floortime - Adi, Partiwi Ngayuningtyas (JOEAI (Journal of Education and Instruction), 2020)
This study aims to improve children's speech ability through the floortime approach and to test the floortime approach to the ability to speak with autistic children in the Pediatricia Mojokerto children's growth and development clinic. This study uses a single subject research (SSR) method, known as single subject research. Provision of Baseline for 8 meeting sessions and intervention for 8 session sessions. The author took a sample of 5 autistic students who have the same characteristics and abilities. The data of this study focuses on the results of the ability to speak autistic children. The results of the study, from the analysis of speech data development in autistic children show a change in tendency from unstable to stable and changes in positive direction. The level of change increased by 40 points indicated on the material labeling objects. Conclusion, there is a significant increase in the ability and speech development of autistic children after being given an intervention through the floortime approach. Keywords: Children with autism, ability to speak, Floortime